The center of a circle whose equation is x^2 +y^2 – 12x – 2y +12 = 0 is (6,1)
<h3>Equation of a circle</h3>
The standard equation of a circle is expressed as:
x^2 + y^2 + 2gx + 2fy + c = 0
where:
(-g, -f) is the centre of the circle
Given the equations
x^2 +y^2 – 12x – 2y +12 = 0
Compare
2gx = -12x
g = -6
Simiarly
-2y = 2fy
f = -1
Centre = (6, 1)
Hence the center of a circle whose equation is x^2 +y^2 – 12x – 2y +12 = 0 is (6,1)
Learn more on equation of a circle here: brainly.com/question/1506955
Answer:
5
Step-by-step explanation:
Vanilla ice cream = 3/5 x 25 = 15
Remaining = 25 - 15 = 10
Mint ice cream = 1/2 x 10 = 5
Remainder = 10 - 5 = 5 = vanilla
Look at the table for the people that used Lithium.
There are 18 relapses, 6 No relapses with a total of 24 people.
The relative frequency for relapse, would be dividing the number of relapses by the total number of people.
This would be D. 18 / 24 = 75%